Impact of Papaya Leaf Juice on the Quality of Landrace and Duroc Cross Boar Spermatozoa in Egg Yolk Citrate Diluent - Andini, Agustin; Setyani, Ni Made Paramita; Uly, Kirenius; Lawa, Alvrado Bire (Journal of Tropical Animal Science and Technology, 2025)
This study aims to evaluate the effect of adding papaya leaf juice added to egg yolk citrate diluting medium (S-KT) to assess its effect on the quality of boar sperm from crosses between landrace and duroc breeds. Fresh semen from boar aged 1.5 who were in good health and had received training in semen collection methods was used in the study. Six treatments and five repetitions were employed in an experimental setting as part of a completely random research design, namely: egg yolk citrate without papaya leaf juice (P0), egg yolk citrate + 0.5% papaya leaf juice (P1), egg yolk citrate + 1% papaya leaf juice (P2), egg yolk citrate + 1.5% papaya leaf juice (P3), egg yolk citrate + 2% papaya leaf juice (P4),  egg yolk citrate + 2.5% papaya leaf juice. All treatments are stored in a coolbox with a temperature of 15-20ºC. Every twelve hours, the spermatozoa's mobility, survival, form, and ability to migrate were assessed. With a motility of 53.00±2.73%, viability of 67.70±1.4%, abnormality of 6.00±0.70%, and survival of 54.60 hours (P<0.05), the P5 treatment with the addition of papaya leaf juice up to 2.5% produced the best outcomes at 48 hours of storage. In comparison to previous treatments, it can be said that adding 2.5% papaya leaf juice to the S-KT dilution medium improved the quality of the liquid semen produced by Landrace and Duroc cross boar